Dietary factors and the risk of lung cancer by epidermal growth factor receptor mutation status and histological subtypes - Yin, Xin; Lai, Gillianne Geet Yi; Seow, Adeline; Tan, Daniel Shao Weng; Lim, Darren Wan-Teck; Seow, Wei Jie (Frontiers in Public Health, 2022)
Background Previous studies have reported differential associations of certain dietary factors such as soy consumption by epidermal growth factor receptor mutant (EGFR +) subtype of non-small cell lung cancer (NSCLC). However, whether the other dietary factors including meat, fruits, and vegetables have differential risks on different histological and molecular subtypes of lung cancer remains unclear. Therefore, we conducted a case-control study to evaluate these associations. Methods A total of 3,170 cases and 4,238 controls from three different studies (Genes and Environment in Lung Cancer Study, Lung Cancer Consortium Singapore Study, and Multi-ethnic Cohort Study) were included. Information on demographics, lifestyle, and dietary consumption was obtained using questionnaires. Diet was assessed by using the number of standard servings of each item consumed per week. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between meat, vegetables, and fruits consumption with lung cancer risk after adjusting for potential confounders. Results We identified a significant inverse association between higher consumption of fruits and the risk of lung cancer (2nd tertile: OR = 0.54, 95%CI = 0.46–0.65; 3rd tertile: OR = 0.77, 95%CI = 0.65–0.91), compared with the lower (1st tertile) consumption of fruits. Higher vegetable consumption was significantly associated with a lower risk of EGFR + lung cancer (OR = 0.69, 95% CI = 0.54–0.88), however, this association was not significant among EGFR wild-type (−) lung cancer. Conversely, higher consumption of total meat (OR = 2.10, 95%CI = 1.58–2.79) was significantly associated with higher lung cancer risk, as compared with the lower consumption group. Conclusions Differential associations between vegetable consumption with EGFR mutation status in NSCLC were found. Further prospective studies are warranted to assess this association and elucidate the biological mechanisms.